24-hour urine composition of Sri Lankan adults and their response to 100 mg dihydrochlorothiazide - Vinayagamoorthy, T (My University, 1980)
In the present study, 205 'normal hospitalised subjects' in the age group 16-60 years were included in a clinical trial to estimate the 24-hour urinary composition. Their response to 100 mg dihydrochlorothiazide was also determined. The study revealed that there is marked difference in the 24-hour urine volume and composition between that observed in the present study and that presented in modern literature; 100 mg dihydrochlorothiazide was found to produce a significant diuretic and natriuretic effect in normal Sri Lankan adults. There is a very high correlation between the volume of urine and the cations in the basal excretion as well as with the standard diuretic. The coefficient of regression of volume on cations in the basal excretion was found to be less than that with the standard diuretic.